Temporomandibular joint synovial chondromatosis accompanying temporal bone proliferation: A case report - Kim, Hak-Sun (Imaging Sci Dent, 2018)
Synovial chondromatosis is a rare metaplastic disease affecting the joints, including the temporomandibular joint (TMJ). Since its symptoms are similar to those of temporomandibular disorders, a careful differential diagnosis is essential. A 50-year-old male patient was referred with the chief complaint of pain and radiopaque masses around the left TMJ on panoramic radiography. Clinically, pre-auricular swelling and resting pain was found, without limitation of mouth opening. On cone-beam computed tomographic images, multiple calcified nodules adjacent to the TMJ and bone proliferation with sclerosis at the articular fossa and eminence were found. T2-weighted magnetic resonance images showed multiple signal-void nodules with high signal effusion in the superior joint space and thickened cortical bone at the articular fossa and eminence. The calcified nodules were removed by surgical excision, but the hypertrophic articular fossa and eminence remained. A histopathological examination confirmed the diagnosis. The patient was followed up few months later without recurrence.